SIMULATION OF MISSILE LAUNCH USING SUKHOI SU-35 AND VYMPEL R-73 3D MODELLING - Federiqo Ervan Novianto Dagomes; Nurcahyani Dewi Retnowati; Anggraini Kusumaningrum (Vortex, 2020)
The simulation is the operations imitating technique or processes that occur in the system and media, which can speed up the understanding of many things including missile launches. Missile launch simulation process on combat aircraft can be operated using computer simulation and application. The simulation is created using unity program and its buttons tested work fine. The results were tested with 10 questions to 10 flight department respondents. The data which is got showed 70.6% approached the process and missile launch function.